Pembuatan Aplikasi Animasi Tuntunan Berpakaian Bagi Wanita dan Pria Muslim Berbasis Android - Rahmi Aryan; Nenna Irsa Syahputri; Sarudin Sarudin (Department of Information Technology, Universitas Timor, Indonesia, 2023)
Dress is one thing that is very important as self-expression and the interaction of the wearer influences how people communicate status, personality, identity, and feelings to others. Dressing also has rules according to Islamic law, namely dressing not transparently, not tight, not the color of the skin and not resembling the opposite sex. Due to the increasing era of globalization, Indonesian people, especially children of the next generation, actually imitate or participate in globalization by dressing that is not appropriate according to Islamic law. Besides that, the era of globalization greatly affects the development of technology. An example of a highly developed technology is Smartphones based on Android. One way to attract people's interest to know how to dress properly in Islam is with animated videos. The Android-Based Dressing Guide Application for Muslim Women and Men was created with two programs, namely Adobe Animate and Herman. The Adobe Animate application is used because it has more complete and up-to-date features and fulfills the need to create Android-based applications. Animated videos are made using Adobe Animate, for audio and backsound using stock background music from the Yottube platform and other supporting websites. The result of this application is an .apk file that is compatible with Android mobile devices. The results of testing this application are expected to provide understanding to children aged 6 years and over about the benefits of dressing according to Islamic law in an attractive and fun format.